Optimizing Social Media Platforms as Information Disemination Media - Melisa Arisanty; Gunawan Wiradharma; Isma Fiani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
As a government agency that plays a central role in regulating the entire state budget and revenue (APBN), the Ministry of Finance needs public support and trust. Therefore, it is necessary to disseminate all government information to the public. One way that can be done is the use of social media as a platform in conveying information to the public. Through research using the constructivist paradigm with a qualitative approach and descriptive content analysis, it is expected to illustrate how the Ministry of Finance optimizes the advantages of each social media platform to disseminate government information to the public. The results of this study are presented in the form of strategies for optimally utilizing social media so that they can be an example for various ministries and other government agencies to support the success of the country's current goal of becoming an Advanced Indonesia.